Use of Edge Computing for Predictive Maintenance of Industrial Electric Motors (2019)
Industrial Internet of Things has become a reality in many kind of industries. In this paper, We explore the case of high quantity of raw data generated by a machine. In the aforementioned case is not viable store and process the data in a traditional Internet of Things architecture. For this case, We use an architecture based on edge computing and Industrial Internet of Things concepts and apply them to a case of machine monitoring for predictive maintenance. The proof of concept shows the potential benefits in real industrial applications. © 2019, Springer Nature Switzerland AG.